#### Answer

$-\frac{4}{7}$

#### Work Step by Step

$(\frac{2}{3})(-\frac{6}{7})=-\frac{2\times6}{3\times7}=-\frac{12}{21}=-\frac{12\div3}{21\div3}=-\frac{4}{7}$

Published by
Pearson

ISBN 10:
0321825535

ISBN 13:
978-0-32182-553-7

$-\frac{4}{7}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.